2019
DOI: 10.1103/physrevphyseducres.15.010102
|View full text |Cite
|
Sign up to set email alerts
|

Classical test theory and item response theory comparison of the brief electricity and magnetism assessment and the conceptual survey of electricity and magnetism

Abstract: For proper assessment selection understanding the statistical similarities amongst assessments that measure the same, or very similar, topics is imperative. This study seeks to extend the comparative analysis between the brief electricity and magnetism assessment (BEMA) and the conceptual survey of electricity and magnetism (CSEM) presented by Pollock. This is accomplished by using large samples (N BEMA ¼ 5368 and N CSEM ¼ 9905) within classical test theory (CTT) and item response theory (IRT) frameworks. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
1
11
2
3
Order By: Relevance
“…It was suggested that the CSEM and BEMA were nearly equivalent in measuring students' understanding of static electricity and magnetism at the introductory level. Recently, Eaton et al corroborated Pollock's findings [18]. The two CIs were compared using both the CTT and IRT approaches.…”
Section: B Comparing Different Cis Targeting Similar Contentmentioning
confidence: 82%
See 2 more Smart Citations
“…It was suggested that the CSEM and BEMA were nearly equivalent in measuring students' understanding of static electricity and magnetism at the introductory level. Recently, Eaton et al corroborated Pollock's findings [18]. The two CIs were compared using both the CTT and IRT approaches.…”
Section: B Comparing Different Cis Targeting Similar Contentmentioning
confidence: 82%
“…Furthermore, although the overall difficulty of CSEM and BEMA has been compared as being equivalent in previous studies [17,18], there is a gap in the literature on finer grained comparisons of individual students' performances on these two CIs which is worth exploring. In addition, this study will produce two short CIs of BEMA, which make a total collection of 6 CIs including short and long versions on electricity and magnetism.…”
Section: B Comparing Different Cis Targeting Similar Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Conforme Eaton et al (2019), que fez aplicações utilizando o BEMA e CSEM, diz que a confiabilidade do teste refere-se à consistência que este teste tem em dar uma nota específica para o respondente; ressalta que valores abaixo de 0,8 fazem com que o teste conceitual esteja apto a relacionar grupos, mas não indivíduos. O Alfa de Cronbach é igual a:…”
Section: Alfa De Cronbachunclassified
“…Many studies have tested these assessments in an attempt to understand the psychometric properties of these tools, see Refs. [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%